First measurement in the Gamow window of a reaction for the γ-process in inverse kinematics: 76Se(α,γ)80Kr - J. Fallis; C. Akers; A.M. Laird; A. Simon; A. Spyrou; G. Christian; D. Connolly; U. Hager; D.A. Hutcheon; A. Lennarz; P. O'Malley; S.J. Quinn; et al. (Physics Letters B, 2020)
The p-nuclei are the few stable nuclei heavier than iron on the neutron-deficient side of the valley of stability that cannot be produced through astrophysical neutron-capture reactions. The limited experimental data on reactions through which the p-nuclei might be produced leaves the origin of their production largely unknown. This work presents the first cross section measurements of the 76Se(α,γ)80Kr reaction. The rate of the time reversed reaction, 80Kr(γ,α)76Se, is one of the most uncertain of possible reactions which can occur at the 80Kr branching point on the γ-process photo-disintegration pathway. The reaction flow through 80Kr will directly affect the final abundance of the p-nuclide 78Kr. Experimental cross sections at two astrophysically relevant energies are reported and compared to cross sections calculated using Hauser-Feshbach codes talys, non-smoker, and smaragd. The success of these first (α,γ) cross section measurements performed in inverse kinematics in the energy region of the γ-process opens the door for future studies of reactions on radioactive γ-process nuclides.